Synthesis of Carbon Dot Nanoparticles (C-Dot) from Seeds and Seedpods of Kesumba Keling (Bixa orellana) using Hydrothermal and Solvothermal Methods - Amrina Rosyada; Sri Sugiarti; Irma Herawati Suparto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
C-dot is a 0-dimensional nanoparticle with photoluminescence properties and can be synthesized from plants, such as the Kesumba Keling plant. Kesumba Keling contains a red pigment sourced from the bixin and norbixin dyes containing functional groups like ‒COOH and ‒COO‒. These functional groups are anticipated to enhance the luminescence intensity produced by C-dot. This research focuses on synthesizing C-dots from Kesumba Keling seeds and seedpods using hydrothermal and solvothermal methods. It also involves an analysis of how different solvents and passivation agents affect the luminescence of C-dots, along with a comparison of the resulting fluorescent colors. The highest yield, at 73.26%, was achieved when using Kesumba Keling seedpods and ethanol as the solvent without adding urea. Furthermore, C-dots synthesized using ethanol as the solvent display a stronger luminescent glow compared to those produced using double-distilled water as the solvent. Additionally, all C-dots synthesized in this study emit a blue luminescence. Characterizing C-dots using a UV-Vis spectrophotometer reveals absorption peaks at two different wavelengths: 260‒280 nm and 320‒340 nm. These absorption peak results align with C-dot characteristics, as confirmed by Fourier transform infrared spectrophotometry. When comparing the intensity of C-dots, those derived from Kesumba Keling peel using the double-distilled water solvent with the addition of urea exhibit a higher intensity (measuring at 0.99) than C-dots obtained from Kesumba Keling peel using ethanol as a solvent with added urea. The solvothermal method is deemed the most effective for C-dot synthesis, as it yields the highest luminescence intensity, accompanied by an emission wavelength shift to 491.65 nm.